Implementation of nanoparticles in diagnostic applications (REVISTA SAYWA, 2021)
Nanodiagnosis allows the identification of diseases in their initial studies at the cellular or molecular level, and ideally at the level of a single cell, through the use of nanodevices and contrast systems. This tool provides a valuable contribution to medicine, since it allows a faster and more accurate diagnosis, offering the possibility of giving a timely and adequate treatment.Nanotechnology provides a fundamental understanding of biological phenomena at the nano-scale. With the implementation of this new technology it is possible to create and manipulate devices and systems with new properties and functions, originated by their nanometric size. This branch has influenced the area of health, whose main objective is to develop tools to diagnose, prevent and treat diseases. Pathologies that can be detected in their initial stage and thus be able to act in a timely manner.